2021
DOI: 10.1007/s13644-021-00461-2
|View full text |Cite
|
Sign up to set email alerts
|

Couple Religiosity, Male Headship, Intimate Partner Violence, and Infidelity

Abstract: Background The research literature finds a positive relationship between couple religiosity and relationship quality, but because public discourse highlights religious victims of domestic violence, we questioned whether couple religiosity prevents negative relationship outcomes as well as it promotes positive ones. Purpose This article compares rates of intimate partner violence (IPV) and infidelity among couples with different levels of religious commitment. We further interrogated whether the belief that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
1
1
Order By: Relevance
“…We were surprised by finding no support for the association between personal religious importance and group membership. Despite evidence suggesting an association between religiosity and EMI ( Dollahite and Lambert, 2007 ; Whisman et al, 2007 ; Whisman and Snyder, 2007 ; Tuttle and Davis, 2015 ; DeRose et al, 2021 ), personal religious importance was not associated with EMI in our study. Likewise, religiosity was not linked to MFD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We were surprised by finding no support for the association between personal religious importance and group membership. Despite evidence suggesting an association between religiosity and EMI ( Dollahite and Lambert, 2007 ; Whisman et al, 2007 ; Whisman and Snyder, 2007 ; Tuttle and Davis, 2015 ; DeRose et al, 2021 ), personal religious importance was not associated with EMI in our study. Likewise, religiosity was not linked to MFD.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, qualitative evidence suggests that religiosity promotes marital fidelity ( Dollahite and Lambert, 2007 ). Quantitative evidence supports the qualitative evidence—religiosity is negatively associated with EMI ( Whisman et al, 2007 ; Whisman and Snyder, 2007 ; Tuttle and Davis, 2015 ; DeRose et al, 2021 ). The second reason that religiosity may reduce marital betrayal is that individuals embedded within a religious community are likely to enforce the norms of that community.…”
Section: Marital Financial Deception and Extramarital Infidelity In S...supporting
confidence: 59%
“…Systematic reviews have compiled a robust database in which the R/S dimension is associated with less perpetration of violence, delinquency, alcoholism, and substance abuse in adolescents 15–17. Several other studies have indicated a protective role of religiosity in intimate partner violence (IPV), in fights and gang affiliations 18–21. Research also showed a potential protective role of religiosity on children when the parents were religious,22–24 which could be due to the moral and spiritual values shared within the home.…”
Section: Introductionmentioning
confidence: 99%